Blood Pressure Classification of 2017 Associated With Cardiovascular Disease and Mortality in Young Chinese Adults. Issue 1 (July 2020) - Wu, Shouling; Song, Yongjian; Chen, Shuohua; Zheng, Mengyi; Ma, Yihan; Cui, Liufu; Jonas, Jost B.
Abstract : The American College of Cardiology/American Heart Association introduced new guidelines for blood pressure (BP) classification in 2017. We explored associations between the newly defined categories and eventual cardiovascular disease (CVD) events, stroke, and all-cause mortality in young Chinese adults. In the community-based Kailuan Study, 16 006 participants aged 18 to 40 years and examined at baseline in 2006/2007 underwent 2-yearly follow-up examinations up to 2016 to 2017. Taking the highest BP reading recorded by manual sphygmomanometry at baseline in 2006 to 2007, we categorized the BP according to the new guidelines. Outcome parameters were CVD events, stroke, and all-cause mortality. During follow-up (mean: 10.9±0.63 years), we observed 458 events (CVD, 167; stroke, 119; and all-cause death, 172). After multivariable adjustment, hazard ratios for CVD events were for elevated BP 0.80 (95% CI, 0.28–2.30), stage 1 hypertension 1.82 (95% CI, 1.12–2.94), and stage 2 hypertension 3.54 (95% CI, 2.18–5.77) versus normal BP. Similar results were obtained for stroke and all-cause death. In Cox regression analysis with BP category entered as time-dependent covariate, stage 1 hypertension was not associated with increased risk ( P >0.10). In the subgroup of individuals taking antihypertensive medication during follow-up, none of the BP categories was significantly associated with the incidence of CVD events. During a mean follow-up of 10.9 years, the newly defined category of stage 1 hypertension in young untreated Chinese adults aged <40 years at baseline was associated with an increased risk for CVD, stroke, and all-cause mortality. This increased risk occurred, however, after progression to stage 2 hypertension. The data may help validating the new BP classification system for young adult Chinese. Abstract : Supplemental Digital Content is available in the text.